2012×2014×【1⼀(2012×2013)+1⼀(2013×2014)】的算法

2012×2014×【1/(2012×2013)+1/(2013×2014)】的算法
2025-02-14 07:22:32
推荐回答(5个)
回答1:

直接展开,化简就可以啦。
2012×2014×【1/(2012×2013)+1/(2013×2014)】

=2012×2014×1/(2012×2013)+2012×2014x1/(2013×2014)

=2014/2013+2012/2013
=(2014+2012)/2013
=(2013x2)/2013
=2

精锐成山王老师

回答2:

先将后面括号里化简开来
2012×2014×[1/(2012×2013)+1/(2013×2014)]

=2012×2014×(1/2012-1/2013+1/2013-1/2014)

= 2012×2014×(1/2012-1/2014)
= 2012×2014×2/(2012×2014)
=2

回答3:

回答4:

2012×2014×【1/(2012×2013)+1/(2013×2014)】

=2012×2014×1/(2012×2013)+2012×2014x1/(2013×2014)

=2014/2013+2012/2013=(2014+2012)/2013=(2013x2)/2013
=2

回答5:

=2014/2013+2012/2013
=4026/2013
=2